Time and the Unconscious - Barbosa, Danielle (2024)
The exploration of time and the unconscious is a multifaceted field that encompasses philosophical, psychoanalytic, and historical perspectives. Time is fundamental to problem-solving and is intricately connected to understanding the unconscious mind. According to Sigmund Freud, memory serves as a repository of experiences that, through repression, is kept beyond conscious awareness yet still influences it. As a result, memory and the unconscious are tied to the past and to psychic time, which differs from chronological time. The unconscious is characterized by its timelessness and nonlinearity, remaining outside temporal order. Freud posits that mnemonic processes are unaffected by time, and the unconscious operates autonomously, independent of the conscious mind. Its complex relationship with time blends various temporalities in a process of ongoing reinterpretation. The unconscious, housing perfect but inaccessible memories that manifest as present-day symptoms, is often blocked to avoid distress and pain, with neurosis emerging from repressed memories. Time within the unconscious serves as both a foundational element of the individual and a potentially disruptive force. The quest to resolve present issues through revisiting the past can create pressure, leading to symptoms and conflicts. Grasping the intricacies of time and the unconscious is crucial for understanding the intricacies of psychic dynamics and the connections between individuals, history, and culture.